A Study on Vector-Based Processing and Texture Application Techniques for 3D Object Creation and Visualization - Donghwi Kang; Jeongyeon Kim; Jongchan Lee; Haeju Lee; Jihyeok Kim; Jungwon Byun (Applied Sciences)
This study proposes a technique for generating 3D objects from Shapefile-based 2D spatial data and converting them to comply with the CityGML 3.0 standard. In particular, the proposed Wise Interpolated Texture (hereafter referred to as WIT) technique optimizes texture mapping and enhances visual quality. High-resolution Z-values were extracted using DEM data, and computational efficiency was improved by applying the constrained Delaunay triangulation algorithm. This study implemented more realistic visual representations using high-resolution orthorectified imagery (hereafter referred to as orthoimages) TIF files and improved data retrieval speed compared to existing raster methods through vector-based processing techniques. In this research, data weight reduction, parallel processing, and polygon simplification algorithms were applied to optimize the 3D model generation speed. Additionally, the WIT technique minimized discontinuity between textures and improved UV mapping alignment to achieve more natural and uniform textures. Experimental results confirmed that the proposed technique improved texture mapping speed, enhanced rendering quality, and increased large-scale data processing efficiency compared to conventional methods. Nevertheless, limitations still exist in real-time data integration and optimization of large-scale 3D models. Future research should consider dynamic modeling reflecting real-time image data, BIM data integration, and large-scale texture streaming techniques.